Cyclodextrin/cellulose hydrogel with gallic acid to prevent wound infection - Pinho, Eva (2014)
Cyclodextrin-based hydrogels have been described as suitable for the controlled-release of bioactive molecules to be used as wound dressing. These materials have major advantages, since they gather the hydrogel properties (high degree of swelling and easy manipulation) and the encapsulation ability of cyclodextrins. β-cyclodextrin (β) or hydroxypropyl-β-cyclodextrin (HPβ) was cross-linked (1,4-butanediol diglycidyl ether) with hydroxypropyl methylcellulose under mild conditions. The hydrogels were chemically characterized by swelling degree, FTIR, DSC and contact angle. The gallic acid loading and release was also analysed, as well the antibacterial activity and cytotoxicity of the polymeric networks. The hydrogels obtained were firm and transparent, with good swelling ability. The gel-HPβ had a surface more hydrophilic when compared with the gel-β. Nevertheless, both hydrogels were capable to incorporate gallic acid and sustain the release for 48 h. The antibacterial activity of gallic acid was maintained after its adsorption within the polymeric matrix, as well as, gallic acid effect on fibroblast proliferation. Therefore, gel-β and gel-HPβ conjugated with gallic acid were shown to be a viable option for antibacterial wound dressing.